2021
DOI: 10.1063/5.0025398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al/Er ratio on the optical properties and structures of Er3+/ Al3+ co-doped silica glasses

Abstract: In this study, Er3+/Al3+ co-doped silica glasses with various Al/Er ratios ranging from 0 to 200 and a constant Er2O3 amount were prepared using the sol-gel method combined with high-temperature vacuum sintering. The absorption, emission spectra, and fluorescence lifetime of Er3+ ions were recorded and the absorption and emission cross sections were calculated. Using Raman, 27Al and 29Si magic angle spinning nuclear magnetic resonance (MAS-NMR), 27Al triple-quantum (TQ)-MAS-NMR, and electron paramagnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In some cases, the glass modifiers have a minor influence on absorption properties but a strong impact on the emission cross-sections attributed to the 4 I 13/2 → 4 I 15/2 near-infrared transition of Er 3+ ions. Recently, it was well demonstrated for Er 3+ ions in silicate glass with various Al 2 O 3 content [ 45 ] and Er 3+ /Yb 3+ co-doped phosphate glass modified by Y 2 O 3 [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the glass modifiers have a minor influence on absorption properties but a strong impact on the emission cross-sections attributed to the 4 I 13/2 → 4 I 15/2 near-infrared transition of Er 3+ ions. Recently, it was well demonstrated for Er 3+ ions in silicate glass with various Al 2 O 3 content [ 45 ] and Er 3+ /Yb 3+ co-doped phosphate glass modified by Y 2 O 3 [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of efficient light emission by RE-doped sol–gel bulk and thin-film glasses has promoted a large number of studies of the way to improve the fluorescence yield in these materials [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. One of the ways to enhance fluorescence is based on aluminum co-doping; its positive effect on the fluorescence properties of RE-doped glasses [ 47 ], and in particular of sol–gel glasses [ 37 , 48 , 49 , 50 ] has been known for a long time, although the physical-chemical mechanism is still an object of research.…”
Section: Sol–gel-derived Silicate Glasses For Photonicsmentioning
confidence: 99%
“…It was suggested that the fluorescence enhancement by Al co-doping was due to different mechanisms, depending on the Al:RE ratio: at low Al concentrations, the site symmetry is lowered, and the transition probability is increased; at a high Al:RE ratio, the highest frequency phonons are of lower energy and therefore nonradiative decay rates are reduced. In another recent study, dealing with Er 3+ /Al 3+ -doped silica glasses with Al/Er ratios from 0 to 200 [ 45 ], it was shown that, as the Al/Er ratio increased, the number of Al 3+ ions around the Er 3+ ions gradually increased, too. Concurrent structural changes led to the site-to-site variations in the erbium local environment and finally to the inhomogeneous broadening of the absorption and emission spectra, with a decrease in both absorption and emission at 1.53 µm.…”
Section: Sol–gel-derived Silicate Glasses For Photonicsmentioning
confidence: 99%
“…However, the development of new generation communication demands for broadband emissions at wavelength longer than 1610 nm (L+ band) furtherly [3]. Besides, EDFA is difficult to achieve a flat and efficient gain spectrum in L+ band due to the characteristics of Er 3+ spectrum in silica glass [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of new generation communication demands for broadband emissions at wavelength longer than 1610 nm (L+ band) furtherly [3]. Besides, EDFA is difficult to achieve a flat and efficient gain spectrum in L+ band due to the characteristics of Er 3+ spectrum in silica glass [4].Instead, among glass hosts, phosphate glass shows many advantages such as mature manufacture technology, high transparency, high doped concentration and large-scale component adjustment [5], [6]. Meanwhile, the spectroscopic properties of Er 3+ in phosphate glass can be widely adjusted by changing the composition [7].…”
mentioning
confidence: 99%